A highly linear 79 GHz Low-Noise Amplifier for Civil-Automotive Radars in 22 nm FD-SOI CMOS with -6 dBm iP1dB and 5 dB NF - Songhui Li; David Fritsche; Laszlo Szilagyi; Xin Xu; Quang Huy Le; Defu Wang; Thomas Kämpfe; Corrado Carta; Frank Ellinger (2021 16th European Microwave Integrated Circuits Conference (EuMIC), 2021)
This paper presents a highly linear 79 GHz differential low-noise amplifier (LNA) for civil-automotive radars operating at the predefined frequency range from 77 GHz to 81 GHz. The circuit is optimized for frequency-modulated continuous-wave (FMCW) radar application, which typically require a very high input-referred 1 dB-compression point (iP 1dB ). A reconfigurable differential common-source stage with capacitive neutralization is employed together with a common-gate stage in cascode configuration as the core of the LNA. The performance of the circuit can be easily adjusted within the gain-NF-P 1dB trade-off boundaries by changing the voltage at the back-gate terminal of the common-source stage, thus tailored to the application specific requirements. Passive baluns are placed at input and output to characterize the differential circuit with the available single-ended laboratory instrumentation. The LNA is implemented in a 22 nm FD-SOI CMOS technology. Its core is very compact with an area of 0.04 mm 2 . The fabricated chip is experimentally characterized in the lab, and it shows a peak gain of 8.7 dB at 80 GHz. From 75 GHz to 85 GHz, the measured input referred P 1dB (iP 1dB ) is about -6 dBm, and the minimum noise figure (NF) is 5 dB. Compared with the state-of-the-art for LNAs operating in a similar frequency range, the presented circuit shows the highest iP 1dB and has the most compact circuit core, together with an excellent NF and a moderate gain, resulting in the best figure-of-merit.